(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the impact of disclosure on the commitment of Zakat and charity payers by examining the role of accounting disclosure and transparency in enhancing taxpayers’ trust in Zakat institutions and increasing their commitment to paying Zakat and charities. The study adopted the descriptive analytical approach and used a questionnaire as the main tool for data collection from a sample of 64 Zakat and charity payers. Several statistical methods were employed to analyze the data, including arithmetic means, standard deviations, and the One-Sample T-Test to test the study hypotheses to verify their statistical significance. The study revealed a statistically significant impact and large effect size (22.286) of disclosure on the commitment of Zakat and charity payers. The results showed that all study dimensions have achieved significance levels lower than 0.05, indicating a positive relationship between disclosure and commitment. The findings also revealed that disclosure and transparency contribute to enhancing trust in Zakat institutions, increasing credibility, and motivating individuals to fulfill their Zakat and charity obligations. The study recommended enhancing financial and administrative disclosure in Zakat institutions, developing transparency systems, utilizing modern electronic methods for presenting financial reports, and strengthening oversight and awareness regarding the importance of disclosure in promoting trust and commitment.